International Tax: Hybrid Mismatch Arrangements and Shortcomings of the OECD BEPS Action 2 Final Report 2015 - Phiri, Golden (Digital Repository of Theses - SSBM Geneva, 2025)
International tax, as the name indicates, deals with taxation across the globe and those that understand and practice it enjoy it, while at the same time those that do not practice it and buy those services hate it. In this study the researcher embarks on a project to investigate Hybrid Mismatch Arrangements and Shortcomings of the OECD BEPS Action 2 Final Report 2015 – Neutralizing the Effects of Hybrid Mismatch Arrangements by incorporating the OECD Table 1.1 – General Overview of the Recommendations. The study is conducted within Multinational Enterprises (MNEs) in South Africa including the mining, manufacturing, and service industry sectors. OECD Table 1.1 is included in the study as a guide to international tax consultants, multinational enterprises’ international tax users, and international tax authorities to mention a few. The study incorporates the positivism paradigm research philosophy thus incorporating the causal research technique. Causal research seeks to understand the cause-and-effect relationship between variables and indicates that a change in one variable directly causes a change in another variable. In this study the researcher philosophizes domestic law represented by Specific recommendations on improvements to domestic law, (Top column 3 of the OECD Table 1.1), as the independent variable and the OECD Recommended Hybrid Mismatch Rules or linking rules, (Top column 4 of the OECD Table 1.1), as the dependent variable, thus depending on domestic law to neutralize the effects of hybrid mismatch arrangements. The researcher refers to Morgan (2013) causal research theories including sufficient causes and necessary causes as the requirement to effect changes between the independent and dependent variables. The study comprises four research questions and objectives with four test items each set to answer each research question and objective. Positivism research requires science thus involving hypothesis testing to confirm reliability and validity of data. Frequency mean and standard deviation are calculated and used to test hypothesis on one hand, and the Breusch Pagan and F-test are incorporated to detect outliers within the variables and data. The study then constructs the simple linear regression and bar graphs to present graphical analyses of the findings. Both primary and secondary findings are presented in the study. The study finds that the South African jurisprudence is not yet ready to respond to the OECD Recommended hybrid mismatch rules or linking rules thus indicating that the OECD BEPS Action 2 Final Report 2015 - Neutralizing the Effects of Hybrid Mismatch Arrangements, has some shortcomings in the South African international tax arena. There is more that must be done by the OECD than the current Recommended Hybrid Mismatch Rules or linking rules to neutralize the effects of hybrid mismatch arrangements within multinational enterprises (MNEs) in South Africa. The study ends with conclusions on the four research questions and objectives; and four recommendations that if acted upon, the OECD Recommended Hybrid Mismatch Rules or linking rules will undoubtedly bear fruitful results.